Profil Asam Amino Sapi Donggala Berdasarkan 13 Gen Pengkode Protein di DNA Mitokondria - Rini Hastarina Suharmadji; Dela Ayu Lestari; Agung Purnomoadi; Sutopo Sutopo; Asep Setiaji (Politeknik Negeri Jember, 2026)
This study aimed to characterize the amino acid profile of the 13 protein-coding genes in the mitochondrial DNA (mtDNA) of Donggala cattle. Genomic DNA was extracted from liver tissue to obtain the complete mitochondrial genome sequence using Next-Generation Sequencing (NGS) technology. The resulting mtDNA sequences were aligned to identify amino acids encoded by the 13 mitochondrial protein-coding genes, namely COX1, COX2, COX3, ATP6, ATP8, ND1, ND2, ND3, ND4, ND4L, ND5, ND6, and CYTB. The results showed that the amino acid profile of the 13 mtDNA protein-coding genes in Donggala cattle was dominated by leucine (Leu), while cysteine (Cys) exhibited the lowest proportion. These findings provide fundamental information on the mitochondrial genetic characteristics of Donggala cattle and may support future studies on the conservation and breeding of local cattle genetic resources.